Higher doses of a green tea-based supplement increase post-exercise blood flow following an acute resistance exercise bout in recreationally resistance-trained college-aged men. Issue 1 (27th May 2020) - Fox, Carlton D.; Garner, Christian T.; Mumford, Petey W.; Beck, Darren T.; Roberts, Michael D.
Abstract: Background: There are animal data suggesting green tea can enhance blood flow. However, human data are lacking. Thus, the purpose of this study was to examine the acute effects of low and high doses of a green tea-based supplement (GBS) on brachial artery blood flow before and following a resistance exercise bout. Methods: In this, double-blinded placebo-controlled trial, college-aged males ( n = 18) who self-reported recreationally resistance training for the previous 6 ± 3 years were assigned to one of two studies including a low (300 mg serving) ( n = 9) or high dose (600 mg serving) ( n = 8; 1 drop) GBS study. During testing sessions, participants reported to the laboratory following an overnight fast and rested in a supine position for 15 min. Thereafter, baseline measurements for resting heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), brachial artery diameter (BAD) and blood flow (BBF) were obtained (PRE). Participants then consumed either their respective GBS dose or a similar placebo dose (microcrystalline cellulose) in a supine resting state. HR, SBP, DBP, BAD and BBF were measured 45 min after placebo or GBS ingestion (PRE2). Participants were then placed in a recumbent position and performed 4 sets of 10 arm curl repetitions using an 11 kg dumbbell. Participants returned to a supine position and HR, SBP, DBP, BAD and BBF were obtained within the first 3 min following exercise (POST), 15 min after exercise (15POST), and 45 min after exercise (45POST). Participants returned to the laboratory 24–48 h later to repeat the same protocol with either GBS or the placebo depending on randomization. Two-way (supplement x time) repeated measures ANOVAs were used to compare dependent variables between testing sessions for Study 1 (300 mg of GBS and placebo) and Study 2 (600 mg of GBS and placebo), and statistical significance was set at p < 0.05. No statistical comparisons were made between studies. Results: As expected, exercise increased BAD and BBF compared to resting baseline measured irrespective of supplementation. In addition, BAD and BBF did not differ between GBS and placebo at any time point after exercise in Study 1. In study 2, however, 600 mg GBS increased baseline-normalized BBF at immediately post exercise compared to placebo (placebo = 211 ± 155% increase, GBS = 349 ± 156% increase; p = 0.012) but not BAD. Conclusions: These data suggest a higher dose of GBS can enhance localized blood flow acutely following a resistance exercise bout. However, the long-term implications of these data are unclear, and more well-powered studies are needed to validate efficacy and elucidate potential mechanisms.